2017
DOI: 10.1016/j.tox.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of TNF/LT locus alters mouse metabolic response to concentrated ambient PM2.5

Abstract: Background Exposure to ambient fine particulate matter (PM2.5) is associated with increased cardiometabolic morbidity and mortality. This is widely believed to be attributable to PM2.5 exposure-induced pulmonary and subsequent systemic inflammation. Tumor necrosis factor alpha (TNFα), lymphotoxin α (LTα), and lymphotoxin β (LTβ) are three homologous pro-inflammatory cytokines, each with both unique and redundant activities in inflammation. Their role in PM2.5 exposure-induced inflammation and adverse cardiomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
6
11
0
Order By: Relevance
“…These clusterings strongly suggest that chronic CAP exposure markedly altered the circulating metabolome. They are consistent with numerous previous studies showing that chronic ambient PM 2.5 exposure correlates with various systemic and/or extra-pulmonary effects (Chen et al, 2017;Chen et al, 2018;Gorr et al, 2014;Hu et al, 2017;Sancini et al, 2014;Zhang et al, 2017). Notably, in spite of those numerous studies investigating the toxicity of chronic ambient PM 2.5 exposure, its biomarker(s) has not yet been established.…”
Section: Discussionsupporting
confidence: 91%
“…These clusterings strongly suggest that chronic CAP exposure markedly altered the circulating metabolome. They are consistent with numerous previous studies showing that chronic ambient PM 2.5 exposure correlates with various systemic and/or extra-pulmonary effects (Chen et al, 2017;Chen et al, 2018;Gorr et al, 2014;Hu et al, 2017;Sancini et al, 2014;Zhang et al, 2017). Notably, in spite of those numerous studies investigating the toxicity of chronic ambient PM 2.5 exposure, its biomarker(s) has not yet been established.…”
Section: Discussionsupporting
confidence: 91%
“…We had three mice in each group with heterogeneous results. Of note, an increase in the expression of any of the aforementioned genes impaired energy metabolism, as demonstrated 20,28,29 .…”
Section: Discussionmentioning
confidence: 81%
“…Previously studies have shown that the inhibition of tumor necrosis factor-alpha (TNF-α) or the use of the IKKβ inhibitor in the hypothalamus of mice chronically exposed to PM 2.5 reduce inflammation in peripheral tissues 16,17,29 . The above studies suggest a link between hypothalamic inflammation induced by PM 2.5 exposure and metabolic dysfunction.…”
mentioning
confidence: 99%
“…Chronic exposure to CAP has been shown to result in glucose intolerance and insulin resistance in various mouse models [ 29 , 30 ]. Figure 1b and c reveal that consistent with these previous studies, the 12-month exposure to CAP versus FA significantly impaired mouse glucose tolerance and induced a marked insulin resistance.…”
Section: Resultsmentioning
confidence: 99%